2016
DOI: 10.1007/s11356-015-5942-0
|View full text |Cite
|
Sign up to set email alerts
|

Sex steroid imbalances in the muricid Stramonita haemastoma from TBT contaminated sites

Abstract: Imposex incidence, organotin tissue levels, and sex steroid (free and esterified testosterone and estradiol) levels were assessed in Stramonita haemastoma from Babitonga Bay (Santa Catarina State, Southern Brazil). The imposex levels showed a reduction when compared to a previous evaluation performed in the same area. In spite of that, the detected imposex incidence indicated the occurrence of tributyltin (TBT) inputs that were still able to produce endocrine disruption in local gastropods. In addition, a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Particularly, within Latin America, a large number of studies have been reported for gastropods in coasts of Chile (Batista et al, 2016;Mattos et al, 2017); Venezuela (Paz-Villarraga et al, 2015); Brazil (Petracco et al, 2015;Rossato et al, 2016); Argentina (Del Brio et al, 2016) and Peru (Castro and Fillmann, 2012). Despite this fact, just a few studies performed monitoring programs of organotin contamination in mussels (Table 4).…”
Section: Butyltin Levelsmentioning
confidence: 99%
“…Particularly, within Latin America, a large number of studies have been reported for gastropods in coasts of Chile (Batista et al, 2016;Mattos et al, 2017); Venezuela (Paz-Villarraga et al, 2015); Brazil (Petracco et al, 2015;Rossato et al, 2016); Argentina (Del Brio et al, 2016) and Peru (Castro and Fillmann, 2012). Despite this fact, just a few studies performed monitoring programs of organotin contamination in mussels (Table 4).…”
Section: Butyltin Levelsmentioning
confidence: 99%
“…In these conditions, while the animals may show a low imposex response, the animals' body burden of organotins could still be high, even higher than in more pristine conditions. Some recent results seems to indicate this possibility with animals presenting high organotins body burden with showing low imposex responses (59, 91). Some aspects of the populations used for biomonitoring have influence on the results, such as genetics, temperature influence on metabolism or even the seasonality of the reproductive cycle, a basic aspect often not considered (92).…”
Section: Endocrine Disruption: Detection and Evaluation Of Effects Inmentioning
confidence: 97%
“…2016). In these cases, environmental impacts were directly associated with coastal areas under the influence of intense maritime activities such as ports, marinas and shipyards Rossato et al, 2016). However, areas of intense ship traffic are usually multi-impacted coastal zones that receive inputs from several harmful substances, producing biological effects either individually or pooled (Moreira et al, 2017).…”
Section: Biometrics and Morphometricsmentioning
confidence: 99%